2020
DOI: 10.5817/cp2020-1-3
|View full text |Cite
|
Sign up to set email alerts
|

Mobile virtual reality distraction reduces needle pain and stress in children?

Abstract: Virtual reality (VR) technology is a remarkably effective method for distracting attention from painful stimuli. This is particularly important for children who undergo painful and stressful medical treatments. The main aim of the present study was to examine whether the type of VR distraction had an effect on reducing pain and stress in children during a short blood sampling treatment, and to investigate the effectiveness of mobile VR. Fifty-seven patients of a pediatric nephrology clinic (Mage = 12, particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 52 publications
3
35
0
Order By: Relevance
“…VR can also assist patients in coping with uncomfortable and even painful medical procedures [ 2 ]. Piskorz et al [ 20 ] found that 36 children whose attentions were distracted by playing or watching VR games during blood sampling reported significantly lower pain and stress than 21 children who did not experience VR.…”
Section: Virtual Reality In Health Carementioning
confidence: 99%
“…VR can also assist patients in coping with uncomfortable and even painful medical procedures [ 2 ]. Piskorz et al [ 20 ] found that 36 children whose attentions were distracted by playing or watching VR games during blood sampling reported significantly lower pain and stress than 21 children who did not experience VR.…”
Section: Virtual Reality In Health Carementioning
confidence: 99%
“…27 VR systems were classified as interactive, meaning that the system afforded interactivity beyond head tracking. Three studies (Gerceker et al, 2020;Gerceker et al, 2021;Piskorz et al, 2020) included both interactive and non-interactive subgroups. The interactive group of VR interventions was diverse; while some merely involved visual effects as the patient focused his or her gaze on a virtual object (e.g., Aydin and Ozyazicioglu, 2019), others involved more interactivity with virtual objects (e.g., Eijlers et al, 2019a) or more demanding tasks and games (e.g., Piskorz and Czub, 2018).…”
Section: Virtual Reality Characteristicsmentioning
confidence: 99%
“…All the non-randomized trials (del Castillo et al, 2019;Piskorz and Czub, 2018;Piskorz et al, 2020;Sullivan et al, 2000) were deemed to have a serious risk of bias. Some of the issues observed in randomized trials were also seen in non-randomized trials, such as lacking pre-specified analysis intentions.…”
Section: Risk Of Bias Within Studiesmentioning
confidence: 99%
See 2 more Smart Citations